2020
DOI: 10.1080/2090598x.2020.1762280
|View full text |Cite
|
Sign up to set email alerts
|

Ureteric stenting vs not stenting following uncomplicated ureteroscopic lithotripsy: A prospective randomised trial

Abstract: Objective: To compare three groups of patients who underwent uncomplicated ureteroscopic lithotripsy (URSL) and to evaluate whether stenting could be eliminated after the procedure, as there is no consensus about whether a ureteric stent should be placed after uncomplicated ureteroscopy for stone retrieval. Patients and methods: In this randomised clinical trial (NCT04145063) 105 patients underwent uncomplicated URSL for ureteric stones. They were prospectively randomised into three groups: Group 1 (34 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Patients in the CSG group exhibited a statistically significant worsening of the following IPSS domains: Frequency, Urgency, Nocturia, Storage Symptoms, Total IPSS Score ( p < 0.001), and QoL ( p < 0.002). Our findings are consistent with those of earlier research where nonstented patients had better outcomes in terms of urgency, frequency, suprapubic pain, hematuria, postoperative discomfort, and analgesic use [ 13 , 14 ]. Moreover, a meta-analysis of nine randomized controlled trials of ureteroscopy stenting was presented by Nabi et al, in which individuals who were stented had a higher rate of UTIs [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Patients in the CSG group exhibited a statistically significant worsening of the following IPSS domains: Frequency, Urgency, Nocturia, Storage Symptoms, Total IPSS Score ( p < 0.001), and QoL ( p < 0.002). Our findings are consistent with those of earlier research where nonstented patients had better outcomes in terms of urgency, frequency, suprapubic pain, hematuria, postoperative discomfort, and analgesic use [ 13 , 14 ]. Moreover, a meta-analysis of nine randomized controlled trials of ureteroscopy stenting was presented by Nabi et al, in which individuals who were stented had a higher rate of UTIs [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previously conducted studies which eliminated the routine use of stents following an uncomplicated URSL demonstrated severe impairment of sexual function in both genders, particularly in males, with reduced IIEF scores; however, this was temporary [ 14 ]. Among women who were stented, individual domains of the FSFI—the Arousal, Orgasm, and Satisfaction subdomains—were statistically lower in the stented group [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of URS surgery increased when stent insertion was performed; in this case there was a statistically significant difference in the duration as compared with no stent insertion. This result is similar to that of research conducted by Netto et al, (14) but contrary to a study conducted by Jeong et al (15) which stated that there was no significant difference in the duration of URS with and without stents. Another study also stated that if the duration of URS with lithotripsy is more than 45 minutes, it can potentially cause postoperative complications in the stent-free group.…”
Section: Discussionsupporting
confidence: 88%
“…Urolithiasis is the communal and oldest diseases of the urinary system. Currently, ureteroscopy is one of the most common procedures among various endourological operations and is performed for a variety of indications, including fragmentation and removal of ureteroscopic stones [12][13] . In 2002, Hoskin et al determined that routine stenting of ureter is unnecessary after uncomplicated ureteroscopic removal of the distal ureteral stone, and the same observation was observed in our study [14][15] .…”
Section: Discussionmentioning
confidence: 99%